2020
DOI: 10.3390/cells9102251
|View full text |Cite
|
Sign up to set email alerts
|

The Primary Cilium of Adipose Progenitors Is Necessary for Their Differentiation into Cancer-Associated Fibroblasts that Promote Migration of Breast Cancer Cells In Vitro

Abstract: Cancer associated fibroblasts (CAFs) are central elements of the microenvironment that control tumor development. In breast cancer, CAFs can originate from adipose progenitors (APs). We, and others, have shown that the primary cilium, an antenna-shaped organelle, controls several aspects of APs’ biology. We studied the conversion of human APs into CAFs by breast cancer cell lines (BCCs). Deletion of the cilium of APs by a pharmacological inhibitor, or by siRNA, allow us to demonstrate that the cilium is necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…This comparison revealed that cilium size was not similar in separate APCs derived from breast tissue of the same patient. Consistent with our previous data highlighting the importance of primary cilium elongation for adipose differentiation [ 26 , 38 ], we can also hypothesize that primary cilium size represents a key determinant in driving cell fate. Population 1 preferentially expressed INHBA and CD142 , two markers that are associated with low adipogenic potential.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This comparison revealed that cilium size was not similar in separate APCs derived from breast tissue of the same patient. Consistent with our previous data highlighting the importance of primary cilium elongation for adipose differentiation [ 26 , 38 ], we can also hypothesize that primary cilium size represents a key determinant in driving cell fate. Population 1 preferentially expressed INHBA and CD142 , two markers that are associated with low adipogenic potential.…”
Section: Discussionsupporting
confidence: 92%
“…The expression of αSMA was preferentially induced in Population 1, indicating that this population was more prone to acquire a myofibroblastic phenotype. We used the “semi” coculture method of APCs and cancer cells that we developed [ 26 ] to evaluate the impact of MCF7 and T47D to trigger the secretome of both cell types to induce the CAF phenotype. This technique allows for the analysis of APC proteins without any interference with cancer cell proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other molecular mechanisms proposed for CAF activation include Notch/Eph-ephrin signaling, ECM composition in the TME, DNA damage, physiological stress, inflammatory stimuli, RTK ligands, and TGFβ-mediated signaling [ 34 ]. Moreover, the primary cilium, a sensory organelle with an exceptionally high receptor density [ 233 ], was shown to play a critical role in the de-differentiation process of adipose progenitors toward a CAF phenotype by mediating TGFβ signaling [ 234 ]. All these studies suggest that diverse pathways are responsible for the activation of CAFs, and the TME is likely the major player in triggering the de-differentiation of ASCs/MSCs into different CAFs, depending on their cellular context and the tumor entity.…”
Section: Mutual Interaction Between Ascs/mscs and Breast Cancer Cellsmentioning
confidence: 99%
“…For example, CAFs could contribute to tumor development by providing oxygen and suppressing the immune cells in the TME [ 10 ]. However, other studies suggest that CAFs can exert a tumor-suppressive impact on the TME [ 11 ]. For example, a previous study discovered that CAFs have a vital suppressive impact on fibrosarcoma [ 12 ].…”
Section: Introductionmentioning
confidence: 99%